Depression among Indonesian citizens in the post-COVID-19 pandemic era: A descriptive survey - Eka Rokhmiati Wahyu Purnamasari; Ronnell D. Dela Rosa (Belitung Raya Foundation, 2022)
Background: Depression is a common medical illness that affects a million of individuals around the world. The prevalence of depression is increased during the COVID-19 pandemic, but little is known if the depression persists in the post-pandemic. Objective: This study aimed to describe the current status of depression among Indonesian citizens in urban areas. Methods: A quantitative descriptive survey was used involving 105 Indonesian citizens conveniently selected from urban areas in Jakarta, Bogor, Tangerang, Depok, and Bekasi (JABODETABEK). Patient Health Questionnaire-9 (PHQ-9) was used for online data collection using Google Forms from 6 September 2022 to 12 September 2022. Descriptive statistics were used for data analysis. Results:  Of the participants, 74.3% had no depression, and 25.7% had mild depression.  Those having mild depression were mainly females, those aged 20-30 years, and those working in the health sector. Conclusion: The study may provide a piece of basic information for healthcare professionals to provide mental health interventions, especially to reduce depression in the communities. However, further studies are needed to confirm the results.